Being a member of an energy community: assessing the financial benefits for end-users and management authority - Panagiotou, Konstantina; Klumpner, Christian; Sumner, M. (2017)
Since 2011, in the context of sustainable development, UK government has been encouraging individuals to work as groups, and now, more than 5,000 community led projects are sprouted across the country, since more than 50% of the UK citizens had expressed their interest to get involved with energy communities if they can potentially reduce their electricity cost. The aim of this study is to quantify the financial benefits for end-users and energy management authority when an energy community is settled up. By simulating possible operating scenarios and by observing and assuming a cost effective power flow/exchange between the individuals, the communal energy storage and the power grid, the finances of each scenario were quantified. Consequently, the electricity cost for the end-users and the incomes for the management authority were monitored and the most financially suitable community energy storage along with the PV penetration were identified.